PENGARUH BEASISWA BIDIKMISI DAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA BIDIKMISI TAHUN ANGKATAN 2014 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SEBELAS MARET SURAKARTA - -, Zahra Nur Afida -; -, Sri Wahyuni -; -, Salman Alfarisy Totalia - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
This research aims to determine: (1) the effect of bidikmisi scholarship and independence learning together of the student achievement of bidikmisi students in the class of 2014 Faculty Of Teacher Training and Education Sebelas Maret University; (2) the effect of bidikmisi scholarships on student achievement in bidikmisi in the class of 2014 of the Faculty Of Teacher Training and Education Sebelas Maret University; and (3) the effect of independence learning of the student achievement of bidikmisi students in the class of 2014 Faculty Of Teacher Training and Education Sebelas Maret University.The research method used in this research is descriptive quantitative. The population in this study were all 2014 Bidikmisi students in the Faculty Of Teacher Training and Education Sebelas Maret University. The selected sample was 84 students with the Proportionate Random Sampling technique. Data collection was carried out by questionnaire technique for data on bidikmisi scholarship and learning independence and documentation techniques for student learning achievement data. The data analysis technique used is multiple linear regression analysis with a significance level of 0.05, then processing the data that has been obtained with the help of the SPSS data program (Statistical Product and Service Solution) version 22.0.The results of the study are as follows: first, there is a significant effect between bidikmisi scholarship and learning independence on the learning achievement of bidikmisi students in the year 2014 in the Faculty Of Teacher Training and Education Sebelas Maret University, as indicated by the value of Fcount = 28.445> Ftable = 2.717. Second, there is a significant positive effect between bidikmisi scholarships on student achievement in bidikmisi in the year 2014 in the Faculty Of Teacher Training and Education Sebelas Maret University, as indicated by the value of tcount = 3.570> t table = 1.989. Third, there is a significant positive effect between learning independence on student achievement in bidikmisi in the year 2014 in the Faculty Of Teacher Training and Education Sebelas Maret University, as indicated by the value of tcount = 3.145> t table = 1.989. The Adjust R Square value is 0.398 so that it can be interpreted that 39.8% of the Bidikmisi student learning achievements in the year 2014 Faculty Of Teacher Training and Education Sebelas Maret University are influenced by bidikmisi scholarships and student learning independence while the rest are influenced by other factors.